Differences in mental health status between individuals living with diabetes, and pre-diabetes in Qatar: A cross-sectional study - Montaha Mahmoud (18067649) (2024)
Aims The aims of this study was to determine the prevalence and to compare depression and anxiety screening scores by type of diabetes: type 2 diabetes mellitus (T2DM), type 1 diabetes mellitus (T1DM), and pre-diabetes. The secondary aim was to examine sex differences in screening scores by type of diabetes. Methods This cross-sectional study was conducted in Doha, Qatar using primary data collection (N = 150), and stratified random sampling at a diabetes primary healthcare center. The study tool collected demographic information and used validated mental health screening tools for depressive symptoms “Patient Health Questionnaire-9 (PHQ-9)", and for anxiety symptoms “Generalized Anxiety Disorder 7 (GAD-7)". Results The prevalence of moderate to severe depressive and anxiety scores was highest in the prediabetes group (20 % and 14 % respectively). There were increased PHQ-9 scores in the pre-diabetes group compared to T2DM (p-value <0.05). No statistically significant differences in depressive symptom scores were found when comparing the pre-diabetes group with T1DM, and T1DM with T2DM. When looking at sex differences, there were no statistically significant differences between T1DM and pre-diabetes males and females, however PHQ-9 and GAD-7 scores in T2DM females were poorer compared to T2DM males. Conclusion The results of our study found patients living with pre-diabetes, and females with T2DM are vulnerable populations who should be screened for mental health disorders. Early screening for mental health disorders for individuals diagnosed with prediabetes, T1DM, and T2DM should be routinely conducted to potentially improve health outcomes. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2023.e23515